Analysis of Factors Related to Implementation 5S/5R - Fathi Marsa At Taqi; Evi Widowati (GLOBAL HEALTH SCIENCE GROUP, 2024)
According to data from the International Labour Organization (ILO), an estimated 374 million workers are affected by non-fatal accidents each year, many of which severely affect workers' ability to work. PT. Sanpak Unggul has implemented 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) but there are still 5S findings, such as there are still materials to be processed that are not neatly arranged, materials are scattered and the equipment used in the manufacturing process is not well organized. This study aims to determine the relationship between age, length of work, level of education and level of knowledge with the application of 5S. This type of research is quantitative with a cross sectional approach with a sample of 83 people taken using a simple random sampling technique, through questionnaires and analyzed using Univariate. The results of the study processed using the chi-square test showed that there was a relationship between the level of education (p value = 0.006) and the level of knowledge (p = 0.009) with the application of 5S, there is no relationship between the variables age (p = 1.000) and length of work (p = 0.386) with the application of 5S. The conclusion of this research is that the level of education and knowledge is related to the implementation of 5S. Increasing the educational level criteria in the recruitment process is one method that can be implemented in companies. Meanwhile, the level of knowledge can be increased by adding pamphlets and training regarding 5S.